ANALISIS PRODUKSI, KONTRIBUSI DAN PERANAN AGRIBISNIS TANAMAN KAKAO RAKYAT DI KABUPATEN ASAHAN - Amran syahputra; Edi Batara Mulya Siregar; Abdul Rahman (JURNAL AGRICA, 2018)
Cocoa is one of the plantation commodity whose role is quite important for the national economy besides oil palm, rubber and coffee. The goal of this research is to analyze the factors that influence the development of cocoa production at Asahan District, To assess the contribution of cocoa commodity in increased revenue of Asahan District, To examine the role of cocoa in increase in employment at Asahan District, ad to assess whether the cocoa can be a commodity in the Asahan District.This use econometric approaches, descriptive and quantitative analysis of the data and the summary of the information and publications related to the cocoa small plantations at Asahan District. From the analysis can be concluded that the increase of cocoa production at  the Asahan District from 1993 until 2007 influenced by factors acreage, productivity and price. The  increase of cocoa production at Asahan District can be implemented by increasing of acreage, number of labor (intensification) and the stimulation of increased the cocoa price. During the analysis period of 7 years, between 2001 and 2007 the cocoa small cultivation at Asahan District is the basis sectors of the economy of Asahan District based on income and employment indicators. The cocoa cultivation influence on regional development in the Asahan District, both to increase the income and employment. The income and employment multiplier obtained from the analysis of the role of commodities in the Asahan District showed the effect of the change in total revenue and employment. Keywords : cocoa, income indicators, approaches econometric